Pengaruh Frekuensi Latihan Fisik Submaksimal Terhadap Kadar Serum Glutamic Pyruvic Transaminase (SGPT) Tikus Putih (Rattus norvegicus) Betina Galur Wistar - Ni Komang Ayu Septia Primayanti (Surabaya Biomedical Journal, 2024)
Abstract According to WHO data (2020), individuals with inadequate physical exercise develop a mortality risk of 20-30% compared to individuals with adequate physical exercise. Regular physical exercise has a positive impact in maintaining a healthy lifestyle, whereas acute intense physical exercise such as in untrained individuals can have a negative impact through the occurrence of oxidative stress. Physical exercise with repetition of exercise can form an adaptation mechanism thereby increasing the work of endogenous antioxidants and inhibiting the formation of ROS. Meanwhile, acute physical exercise without repetition of exercise can cause a decrease in endogenous antioxidant levels and an increase in ROS. Increased ROS induces oxidative stress, which then plays a role in liver damage. This study aims to determine the effect of submaximal physical exercise frequency on SGPT levels, an indicator of liver damage. This research was a laboratory experimental study with a post-test only control group design using 27 Wistar female white rats which were divided into 3 groups; K1 was given standard feed for 4 weeks, K2 was given standard feed for 4 weeks, submaximal physical exercise on days 1 to 14 and 21 of the study, and K3 was given standard feed for 4 weeks and submaximal physical exercise on day 21 of the study. After intervention, all groups of rats were taken for blood to calculate SGPT levels and then the results of the data were analyzed statistically. The results of the Kruskal-Wallis test showed a significance of 0.479 (p>α) with α=0.05, which means that there was no significant difference in the frequency of submaximal physical exercise on SGPT levels in female Wistar rats (Rattus norvegicus). The conclusion of this study showed that there was no effect of the frequency of submaximal physical exercise on SGPT levels in female Wistar rats (Rattus norvegicus).